Advancing neodymium single-band nanothermometry. Issue 23 (5th June 2019) - Skripka, A.; Morinvil, A.; Matulionyte, M.; Cheng, T.; Vetrone, F.
Abstract : Nd 3+ doped LiLuF4 nanoparticles are explored as photoluminescent nanothermometers and imaging probes. Such host-dopant configuration permits to resolve the fine Stark structure of Nd 3+ photoluminescence at 1050 nm, and to use it for subcutaneous temperature sensing. Abstract : Near-infrared (NIR) emitting contrast agents with integrated optical temperature sensing are highly desirable for a variety of biomedical applications, particularly when subcutaneous target visualization and measurement of its thermodynamic properties are required. To that end, the possibility of using Nd 3+ doped LiLuF4 rare-earth nanoparticles (RENPs) as NIR photoluminescent nanothermometers is explored. These RENPs are relatively small, have narrow size distribution, and can easily be core/shell engineered – all combined, these features meet the requirements of biologically relevant and multifunctional nanoprobes. The LiLuF4 host allows to observe the fine Stark structure of the 4 F3/2 → 4 I9/2, 4 I11/2, and 4 I13/2 optical transitions, each of which can then be used for single-band NIR nanothermometry. The thermometric parameter defined for the most intense Nd 3+ emission around 1050 nm, shows high temperature sensitivity (∼0.49% °C −1 ), and low temperature uncertainty (0.3 °C) as compared to the thermometric parameters defined for the 880 and 1320 nm Nd 3+ emissions. Additionally, transient temperature measurements through tissue show that these RENPs can be used to assess fast temperature changes at a tissue depth of 3 mm, while slower temperature changes can be measured at even greater depths. Nd 3+ doped LiLuF4 RENPs represent a significant improvement for Nd 3+ based single-band photoluminescence nanothermometry, with the possibility of its integration within more sophisticated multifunctional theranostic nanostructures.